Abdominal hysterectomy and postoperative quality of recovery: emphasis on pain relief - Lakhno, I; Korovai, S; Zheleznyakov, O; Novikova, O (Pain medicine, 2022)
Hysterectomy is a widespread surgical intervention in gynecological practice. Open abdominal hysterectomy is accompanied by a significant algogenic afferent impulse from the site of surgical intervention. Therefore, the search for effective methods of combating postoperative pain is quite urgent. The article analyzes modern approaches to the preventive (preoperative) use of non-narcotic drugs for reliable pain control. Literature data suggest that the combined use of paracetamol, dexketoprofen, nalbuphin, as well as ropivacaine or bupivacaine allows to implement the concept of multimodal analgesia and optimize the recovery process after surgery. The clinical case is given as an example of the use of the specified Step-UP-analgesia of the postoperative period in an overweight patient with varicose veins of the lower extremities and severe history of septic shock. The review of literature and the experience of the authors testify to the considerable potential of multimodal anesthesia following abdominal hysterectomy.